Validity and reliability of CDAI in comparison to DAS28 in Iraqi patients with active rheumatoid arthritis - Gorial, Faiq I. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Rheumatoid arthritis (RA) disease activity plays a central role in causing disability both directly and via indirect effects mediated through joint damage. Evaluation of RA disease activity is therefore important to predict the outcome and effectiveness of therapeutic interventions during follow-up. Clinical disease activity index (CDAI) is new simple tool for measurement of disease activity. Objectives: To assess validity and reliability of CDAI in comparison to disease activity score-28 joints (DAS28) in Iraqi patients with active RA. Patients and Methods: Sixty nine Iraqi RA patients were included in this study. All patients were fulfilling the ACR classification criteria and active. Full history was taken and complete clinical examination was done for all patients. Patients’ age, sex, duration of the disease, number of tender joints, number of swollen joints, patient’s and physician’s (evaluator) global assessment by visual analogue scale (VAS) (0–10 cm) were recorded. Laboratory analysis included erythrocyte sedimentation rate (ESR). CDAI and DAS28 were measured to assess disease activity. Results: Of 69 patients included in this study, there were 58 women and 11 men. Mean age of the patients was 45.65±12.26 years and mean duration of disease was 7.75±7.85 years. Mean DAS28 and CDAI were 5.86±1.24 and 30.07±14.07respectively.There was direct significant correlation between CDAI and DAS28 (r= 0.879, P< 0.001). Also we found good agreement between CDAI and DAS28 (Kappa = 0.795, P < 0.001). CDAI had sensitivity 90%, specificity 92%, Likelihood ratio (LR) 45.67, Area under the curve (AUC) 0.983 [95% confidence interval (CI) 0.933-1.000] (P value < 0.001). Conclusions: CDAI is a valid and reliable measure for assessment of Iraqi patients with active RA in comparison to DAS28.